1970
DOI: 10.3126/kumj.v6i4.1741
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti HCV antibodies among blood donors in Kathmandu valley, Nepal

Abstract: Aims and objectives: To study the seroprevalence of anti HCV antibodies among Nepalese blood donors in relation to their age, sex, type of donation and times of donation. Materials and methods: Descriptive cross-sectional study conducted in Nepal Red Cross Society (NRCS), Central Blood Transfusion Service (CBTS), Kathmandu, from December 1, 2006 to September 1, 2007. A total of 33,255 blood donors were screened for anti HCV antibodies by ELISA. Donor's information was collected from blood donor's record form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
3
21
3
Order By: Relevance
“…Differences in HIV, HBV, HCV and Syphilis seroprevalence in Nepal compared to studies conducted in Ethiopia [1], Tanzania [22], Thailand [23] and Pakistan [24] must have been due to variations in geographical distribution as well as population differences in terms of lifestyle, awareness, sensitivity and specificity of tests, donor selection criteria, etc. The prevalence of HIV, HCV, and HBV also seems to be decreasing when compared to similar previous studies focussed on any of these infections conducted in Kathmandu, Nepal [5,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Differences in HIV, HBV, HCV and Syphilis seroprevalence in Nepal compared to studies conducted in Ethiopia [1], Tanzania [22], Thailand [23] and Pakistan [24] must have been due to variations in geographical distribution as well as population differences in terms of lifestyle, awareness, sensitivity and specificity of tests, donor selection criteria, etc. The prevalence of HIV, HCV, and HBV also seems to be decreasing when compared to similar previous studies focussed on any of these infections conducted in Kathmandu, Nepal [5,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 80%
“…Mandatory screening tests are performed for human immunodeficiency virus (HIV) 1 and 2, hepatitis B virus (HBV), hepatitis C virus (HCV) and syphilis by blood transfusion centres in Nepal. HIV seroprevalence among blood donors in different regions of Nepal and Kathmandu Valley has been reported to range from 0.019% to 0.41% [4][5][6][7]. HBV seroprevalence has been reported to range from 0.3% to 4.0% in the general population of Nepal by various studies conducted from 1990 to 2003 [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Each participant was informed of their test individually. In study, the past medical history of patients was taken since 2002 to 2012 till now, and regarding Nepal Blood Bank, Annual Progress Report of medical year 2011/012 is accessed for reference [19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…3 Different studies from Nepal showed that the sero-prevalence of HCV ranges from 0.35% to 1.73% in blood donors and healthy population with highest prevalence among injection drug users. [4][5][6][7][8] Six different HCV genotypes and multiple subtypes have been identified on the basis of molecular relatedness. …”
Section: Introductionmentioning
confidence: 99%